Rapid generation of chemical combinations on a magnetic digital microfluidic array - Zhang, Yi (2019)
Combinatorial screening is frequently used to identify chemicals with synergistic effects by measuring the response of biological entities exposed to various chemical-dose combinations. Conventional microwell-based combinatorial screening is resource-demanding, and the closed microfluidics-based screening requires sophisticated fluidic control systems. In this work, we present a novel combinatorial screening platform based on the surface energy trap (SET)-assisted magnetic digital microfluidics. This platform, known as FlipDrop, rapidly generates chemical combinations by coupling two droplet arrays with orthogonal chemical concentration gradients with a simple flip. We have illustrated the working principle of FlipDrop by generating combinations of quantum dots. We have also successfully demonstrated the screening of quantum dot fluorescence resonance energy transfer (QD-FRET) on the FlipDrop platform by measuring the FRET response. This report demonstrates that FlipDrop is capable of rapidly generating chemical combinations with unprecedented ease for combinatorial screening.